Wukirsari Village as a prestigious tourism village in Yogyakarta - Ajie Wicaksono; John Joi Ihalauw; Sony Heru Priyanto (Privietlab, 2025)
This research aims to identify the potential of Wukirsari village as one of the leading tourist village destinations in Yogyakarta. This village has various awards such as being the best tourist village in the world in 2024 and ADWI awards as the first winner of the Advanced Tourism Village Category. In addition, Wukirsari village is included in the 75 best tourist villages in Indonesia out of 4,537 tourist villages throughout Indonesia. In 2023, this village recorded a MURI record with the most batik artisans. This study uses a qualitative descriptive method. Data collection techniques include interviews, observations, and documentation. To identify the potential of Wukirsari village, this study uses the basis of the tourism component category, namely 4A (Attraction, Accessibility, Amenities, and Ancillary) which each of which is detailed its elements which include 5W (what to see, what to do, what to buy, what to arrive, and what to stay). Data analysis uses qualitative analysis which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the tourism component in Wukirsari village has been fulfilled, which includes 4A (Attraction, Accessibility, Amenities, and Ancillary). Attractions are divided into natural tourism, cultural tourism, and artificial tourism. Natural attraction is the flagship of this village. Morphologically, Wukirsari village is in the form of hills that are passed by the Opak Fault. This village is also developed as a cultural heritage area. With the tourism options owned, especially the natural potential, tourists can enjoy by not only seeing (what to see), but also doing various tourist activities (what to do). The existence of tourist attractions is also supported by tourism components, namely accessibility, facilities (restaurants, lodgings, etc), and additional services (ATMs, health centers, etc).